The Effect of Wind Speed on Structural Along-Wind Response of a Lighting Pole According to TS498 and Eurocode 1 - Erdem Türkeli; Deniz Cokli (Buildings)
This study aimed to determine the wind loads of a steel lighting pole using TS498 and Eurocode 1 standards and to perform structural wind load analyses by applying these wind loads. In this regard, a 10 m high steel lighting pole, whose dynamic structural verification was carried out using the operational modal analysis method, was selected from the technical literature as an application example and was modeled with this verification using the SAP2000 structural analysis program. Comparative structural wind load analysis was carried out by applying the wind loads obtained using the cited standards for different wind speeds (5 mph, 40 mph, and 100 mph) to the modeled lighting pole. The most important novelty of this study from other studies and the innovation it adds to the technical literature is that the effect of wind speed on the dynamic properties of the structure such as frequency and so on wind forces are taken into account. While, in other studies, the dynamic properties of the structure are taken as constant at different wind speeds, in this study, the dynamic properties of the structure vary with the wind speed, which provides an approximately 11~12% reduction in the top displacements for both standards and leads to an economical design.